Penerapan Metode Tutor Sebaya sebagai Upaya Peningkatan Kemampuan Membaca Al-Qur’an Peserta Didik di SMK Negeri 2 Karanganyar - Kamelia, Afi Mika Nada; Inayati, Nurul Latifatul (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
Peer teaching method is one of the methods used in learning of read the Al-Qur’an at SMK Negeri 2 Karanganyar. Peer teaching is a learning method by appointing or assigning students who have mastered a lesson to help their friends who don’t uderstand the subject matter or friends who have difficulty understanding the material. This method involves students to assist teachers in teaching read the Al-Qur’an. Students who have been selected by the teacher will teach their friend to read the Al-Qur’an. The purpose of the study is to describe the application of the peer teaching method in increasing student’s skill in reading the Al-Qur’an at SMK Negeri 2 Karanganyar. This research includes field research with qualitative approach. Data collection techniques were carried out by interviews, observation, and documentation. The results of this study are in to inform of description of implementation of the peer teaching method from data collecton to evaluation, constraints in the practice off  the peer teaching method, and programs that use the peer teaching method as a learning method.